Transformasi Status PT Perorangan Ke PT Konvensional dalam Perspektif Hukum Positif dan Fikih Muamalah - Cahya, Ayuni Nilam; Lutfi, Anas; Ahmad, Suparji (Tasyri' : Journal of Islamic Law, 2025)
The change in the status of an Individual Limited Liability Company (PT) to a Conventional PT is a response to the need for legal adjustments for Micro and Small Enterprises (MSEs) that are experiencing business growth. This phenomenon emerged with the enactment of the Job Creation Law which provides ease of establishing a single legal entity, but poses new problems in terms of accountability and governance. This research uses a juridical normative approach with an analysis method of applicable laws and regulations and the integration of the principles of jurisprudence such as mas'uliyyah (responsibility), shirkah (business partnership), and maqāṣid al-syarī'ah (sharia goals). The results of the study show that the transformation of the status of a PT has a significant impact on the organizational structure and legal validity of the company, and demands the application of the principles of asset separation and business transparency that are in line with Islamic values. This study concludes that the change of status from an individual PT to a conventional PT is a strategic step that not only strengthens the legal position of business actors in the eyes of the state, but also brings business practices closer to the principles of justice, responsibility, and benefit as taught in Islamic law.